Different effects of feeding pregnant and lactating mice Rhodiola kirilowii aqueous and hydro-alcoholic extracts on their serum angiogenic activity and content of selected polyphenols - Robert Zdanowski; Ewa Skopińska-Różewska; Jacek Wilczak; Anna Borecka; Aneta Lewicka; Sławomir Lewicki (Central European Journal of Immunology)
Angiogenesis plays an important role in many physiological processes, among them the formation of tissues and organs during embryogenesis. A lot of medicinal plants exhibit angiomodulatory properties. This creates the need for a thorough check of whether the plant extracts that we would like to give to pregnant women in order to increase their resistance to bacterial or viral infection will have negative effects on angiogenesis, and consequently on fetal development. This paper seeks to investigate the effect of serum of pregnant and nursing Balb/c mice that received aqueous (RKW) or hydro-alcoholic (RKW-A) R. kirilowii extracts (20 mg/kg), or epigallocatechin (0.2 mg/kg), on the in vitro proliferation and migration of mouse endothelial cell line HECa10. Of the 15 identified polyphenols in the extracts by HPLC, 8 were present in the sera. Chemical analysis revealed higher salidroside, kaempferol, chlorogenic acid, bFGF and VEGF concentration in RKW-A sera than in the sera of RKW group of mice. RKW-A and EGC sera did not affect migration of endothelial cells, however we noted some increase of migrating cells after RKW-sera treatment. RKW and EGC sera did not affect proliferation of endothelial cells. Sera of mothers from RKW-A group impaired the proliferation of endothelial cells in comparison to other groups. These data allow us to assume that Rhodiola kirilowii hydro-alcoholic extract (RKW-A) is potentially able to modulate pre- and post- natal angiogenesis what might influence the development of organs in progeny. Sera of RKW mothers have not harm the proliferation of endothelial cells, despite they also contain antiangiogenic catechins and salidroside. This suggests the existence in RKW-A extract and in RKW-A sera of some other, as yet unidentified substances influencing endothelial cells proliferation.